HUNTING FOR SOLOMON'S RING IN SALT ISLAND: THE HISTORY OF HADRAMI DIASPORA IN SUMENEP, 1832-1901 - Rahmat Hidayat; Ahmad Athoillah (Satmata: Journal of Historical Education Studies, 2024)
This article aims to narrate historically the social transformation and economic behavior of the Arab-Hadrami colony in Sumenep. Therefore, a socio-economic historical approach is employed in this research. The researcher engages in archival accuracy, synthesizing data, and presenting it within a historiographical framework. The study findings reveal that the formation of the Arab colony in Sumenep is attributed to the paternalistic relationship established between Arab-Hadrami traders and Sultan Abdurrahman. Socially and religiously based relationship facilitated the migration of Arab traders to Sumenep while also creating economic prosperity for them. However, following the Sultan's demise, the social ties between the Sumenep nobility and Arab traders began to diminish. Secondly, the colonial government's reorganization of Sumenep successfully opened up the island of Madura to the international market through the salt commodity.  On the other hand, the reorganization of Sumenep stimulated the mobility of Arab-Hadrami trade, opening up new economic spaces such as maritime trade and salt transportation for them, and establishing capitalist relationships between Arab-Hadrami traders and the Sumenep nobility through the credit system.